Mercury adsorbent based on sulfur abundance regulation and preparation method and application thereof

By adjusting the molar ratio of molybdenum to sulfur, sulfur-poor and sulfur-rich mercury adsorbents were prepared, solving the problem of insufficient adsorption capacity and selectivity of molybdenum sulfide-based materials in strongly acidic wastewater, and achieving high capacity and high selectivity Hg2+ adsorption effect.

CN122499748APending Publication Date: 2026-08-04CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610600502.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-04-30
Publication Date
2026-08-04

AI Technical Summary

Technical Problem

Existing molybdenum sulfide-based adsorbents are prone to collapse and protonation of active sites in strongly acidic wastewater, resulting in a significant decrease in adsorption capacity. Furthermore, they lack selectivity for Hg2+, making it difficult to achieve high capacity and high selectivity adsorption.

Method used

By adjusting the molar ratio of molybdenum to sulfur in the precursor, sulfur-poor and sulfur-rich mercury adsorbents were prepared. The sulfur-poor mercury adsorbent exposed active sites through sulfur vacancy defects and amorphous structures, while the sulfur-rich mercury adsorbent exposed active sites through lattice defects and two-dimensional nanosheet assembly, thus achieving efficient adsorption of Hg2+.

Benefits of technology

The sulfur-poor mercury adsorbent achieved an adsorption capacity of 2900 mg/g and a partition coefficient Kd of 2.0 × 10⁶ mL/g at pH 2, while the sulfur-rich mercury adsorbent achieved an adsorption capacity of 3900 mg/g and a partition coefficient Kd of 1.0 × 10⁸ mL/g at pH 2, demonstrating high selectivity and adaptability to acidic environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122499748A_ABST
    Figure CN122499748A_ABST
Patent Text Reader

Abstract

The application provides a mercury adsorbent based on sulfur abundance regulation and a preparation method and application thereof. The mercury adsorbent is a sulfur-poor type or a sulfur-rich type, and is prepared from precursors with a molybdenum-sulfur molar ratio of 1:1-8:1 or 1:3-1:30 through a hydrothermal reaction. The sulfur-poor type has an amorphous structure with sulfur vacancy defects, and the sulfur-rich type has a three-dimensional flower-like morphology. The application realizes the synergistic unity of high capacity, strong acid adaptability and high selectivity through sulfur abundance regulation, and is particularly suitable for deep mercury removal of non-ferrous metal smelting waste acid wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of separation technology, specifically relating to a mercury adsorbent based on sulfur abundance regulation, its preparation method, and its application. Background Technology

[0002] Non-ferrous metal smelting processes generate large amounts of acidic wastewater, which is characterized by extremely low pH values ​​(typically less than 2, and even reaching 0), high concentrations of mercury ions (up to hundreds of mg / L), and complex coexisting ion systems. Efficient mercury removal is a key challenge in the treatment of smelting acidic wastewater. Adsorption methods, due to their ease of operation, controllable cost, and wide applicability, are considered one of the most promising technologies for mercury pollution control.

[0003] In existing technologies, adsorption materials used for treating mercury-containing wastewater mainly include traditional adsorbents such as activated carbon, biomass, zeolite, and resin, as well as novel adsorbents developed in recent years such as metal sulfides and metal-organic frameworks. Among them, molybdenum disulfide, as a typical two-dimensional transition metal chalcogenide, exhibits unique advantages in the adsorption of heavy metal ions due to its layered structure and abundant sulfur active sites. However, existing research on molybdenum disulfide-based adsorbent materials mainly focuses on the morphology or crystal phase control of materials, and generally suffers from the following technical problems: First, under the strong acidic conditions (pH < 3) characteristic of acidic wastewater, the material structure is prone to collapse and the active sites are prone to protonation, leading to a significant decrease in adsorption capacity or even complete deactivation; second, in the complex multi-ion coexistence system of acidic wastewater, the adsorption capacity for Hg is limited. 2+ Insufficient selectivity, highly susceptible to Pb 2+ Cd 2+ Fe 3+ As 5+ Strong interference from coexisting ions; finally, conventional mercury adsorbents have limited surface active sites, making it difficult to achieve effective treatment of Hg. 2+ It has an extremely high adsorption capacity, while the adsorption capacity of mercury is generally less than 500 mg / g.

[0004] Based on the above, there is an urgent need for a mercury adsorption material that combines high selectivity, adaptability to acidic environments, and high capacity. Summary of the Invention

[0005] To address the technical problem that mercury adsorption materials in the aforementioned commonly used technologies struggle to simultaneously achieve high selectivity, adaptability to acidic environments, and high capacity, this invention provides a mercury adsorbent based on sulfur abundance regulation. This adsorbent can be either a sulfur-poor mercury adsorbent or a sulfur-rich mercury adsorbent. The sulfur-poor mercury adsorbent is prepared by hydrothermal reaction from a precursor with a molybdenum-sulfur molar ratio of 1:1 to 8:1, while the sulfur-rich mercury adsorbent is prepared by hydrothermal reaction from a precursor with a molybdenum-sulfur molar ratio of 1:3 to 1:30. The sulfur-poor mercury adsorbent has an amorphous or short-range ordered structure with sulfur vacancy defects, exhibiting a nanoparticle stacking morphology. The sulfur-rich mercury adsorbent is assembled from two-dimensional nanosheets with lattice defects distributed on the basal surface to form three-dimensional flower-like microspheres.

[0006] Furthermore, the mercury adsorbent with low sulfur content has a mercury adsorption capacity ≥2900 mg / g and a partition coefficient K. d ≥2.0×10 6 mL / g; The mercury adsorption capacity of the sulfur-rich mercury adsorbent is ≥3900 mg / g, and the partition coefficient K d ≥1.0×10 8 mL / g.

[0007] Furthermore, the Mo / S atomic ratio on the surface of the sulfur-poor mercury adsorbent is 0.1-0.5:1, and the Mo atoms on the surface contain a certain amount of Mo. 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%, and the sulfur atoms on the surface contain S2 2- The proportion is 10-40%, S 2- The proportion is 50-80%, SO4 2- The proportion is 2-10%; The surface Mo / S atomic ratio of the sulfur-rich mercury adsorbent is 1:2.4-5.5, and the Mo atoms in the surface molybdenum atoms are... 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%; S2 in surface sulfur atoms 2- The proportion is 20-50%, S 2- The proportion is 48-65%, SO4 2- The proportion is 10-15%.

[0008] This invention provides a method for preparing the mercury adsorbent as described above, comprising the following steps: The precursor is obtained by mixing a molybdenum source with a sulfur source; the molar ratio of molybdenum to sulfur in the precursor is 1:1-8:1 or 1:3-1:30. The precursor is subjected to a hydrothermal reaction to obtain either the sulfur-poor mercury adsorbent or the sulfur-rich mercury adsorbent.

[0009] Furthermore, the hydrothermal reaction is carried out at a temperature of 100-250°C for a duration of 1-20 hours.

[0010] This invention provides an application of the mercury adsorbent as described above or prepared by the method described above in the treatment of mercury-containing wastewater, comprising the steps of: contacting the mercury adsorbent with the mercury-containing wastewater to adsorb Hg in the mercury-containing wastewater. 2+ .

[0011] Furthermore, the pH of the mercury-containing wastewater is ≥0.

[0012] Furthermore, the mercury-containing wastewater includes coexisting ions; When the mercury adsorbent is a sulfur-rich mercury adsorbent, the mercury-containing wastewater includes Cu. 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Cr 3+ At least one coexisting cation, or Cl - F - HCO3 - PO4 3- At least one coexisting anion.

[0013] Furthermore, the mercury-containing wastewater includes coexisting ions; When the mercury adsorbent is a sulfur-poor mercury adsorbent, the coexisting cations include Cu. 2+ Co 2+ Ni 2+ Zn 2+ Cd 2+ Mn 2+ Fe 3+ Cr 3+ As 5+ At least one of them, or selected from Cl - F - HCO3 - PO4 3- At least one coexisting anion.

[0014] Furthermore, the Hg in the mercury-containing wastewater 2+ The concentration of mercury is ≤2000mg / L, the dosage of the mercury adsorbent is 0.01-2g / L, the contact time between the mercury adsorbent and the mercury-containing wastewater is 5-600min, and the contact temperature is 0-100℃.

[0015] Compared with the prior art, the present invention has at least the following advantages: This invention provides a sulfur-poor mercury adsorbent that, by reducing the sulfur abundance of the precursor, induces the formation of sulfur vacancy defects and amorphous or short-range ordered structures in the material, resulting in a nanoparticle stacking morphology. This structural feature exposes a large number of unsaturated active sites and edge defects on the material surface.

[0016] During the adsorption process, the sulfur-poor mercury adsorbent passes through the lattice sulfur (S) 2- ) and low-priced molybdenum (Mo 4+ The synergistic effect of ) achieves the effect on Hg 2+ Capture and fixation: On the one hand, S 2- With Hg 2+Strong chemical coordination occurs to form stable HgS compounds; on the other hand, Mo... 4+ As an electron donor, it participates in redox reactions, transferring some Hg 2+ Reduced to elemental mercury (Hg) 0 ).

[0017] The sulfur-poor mercury adsorbent combines high selectivity, adaptability to acidic environments, and high capacity. High capacity: at pH=2, Hg 2+ Under an initial concentration of 200 mg / L, the equilibrium adsorption capacity of the mercury-poor sulfur adsorbent reaches over 2900 mg / g, with a partition coefficient K. d 2.55×10 6 mL / g, which is much higher than that of conventional adsorption materials.

[0018] Adaptability to acidic environments: Under extremely acidic conditions with pH=0, the sulfur-poor mercury adsorbent can still maintain a removal rate of about 60% and an adsorption capacity of more than 960 mg / g, demonstrating excellent resistance to strong acids.

[0019] High selectivity: Hg in most binary systems 2+ Maintaining a removal rate of over 80%, it is suitable for treating mercury-containing wastewater with few or low concentrations of coexisting interfering ions.

[0020] This invention provides a sulfur-rich mercury adsorbent that, by increasing the sulfur abundance of the precursor, induces the formation of a two-dimensional layered structure with an interlayer spacing of 0.85-0.95 nm. The basal surface of this structure contains lattice-defect-laden two-dimensional nanosheets assembled to form three-dimensional flower-like microspheres. This structural feature exposes a vast number of unsaturated active sulfur sites in the material.

[0021] During the adsorption process, the sulfur-rich mercury adsorbent employs a unique dual mercury fixation mechanism: on the one hand, the highly active S2... 2- Groups and Hg 2+ Strong covalent coordination occurs, forming stable β-HgS (decomposes at 190℃) and α-HgS (decomposes at 305℃); on the other hand, Mo... 4+ Using low-valence sulfur species as electron donors, some Hg 2+ In-situ reduction to elemental mercury (Hg) 0 ).

[0022] Mercury-sulfur-rich adsorbents combine high selectivity, adaptability to acidic environments, and high capacity. High capacity: at pH=2, Hg 2+ Under an initial concentration of 200 mg / L, the equilibrium adsorption capacity of the mercury-rich sulfur adsorbent is as high as 3900 mg / g or more, with a partition coefficient K. d Reaching 1.67×10 8 mL / g.

[0023] Adaptability to acidic environments: Under extremely acidic conditions with pH=0, the sulfur-rich mercury adsorbent can still maintain a removal rate of about 60% and an adsorption capacity of more than 960 mg / g, breaking through the technical bottleneck of traditional adsorbent materials being easily deactivated under strong acid.

[0024] High selectivity: in Cu-containing 2+ Co 2+ Ni 2+ Zn 2+ Cd 2+ Mn 2+ Fe 3+ Cr 3+ As 5+ In a binary or multi-component mixed system containing at least one coexisting cation, the sulfur-rich mercury adsorbent has a positive effect on Hg. 2+ The removal rate remained consistently above 90%, except for Pb, which also exhibits soft acid properties. 2+ There is approximately 20% co-adsorption, exhibiting excellent mercury ion-specific selectivity. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0026] Figure 1 These are scanning electron microscope (SEM) images of mercury adsorbents with different molybdenum-sulfur ratios in embodiments of the present invention; wherein, Figure 1 (a) is a SEM image of Mo8S1 in the embodiment; Figure 1 (b) is a SEM image of Mo2S1 in the embodiment; Figure 1 (c) is a SEM image of MoS2 in the example; Figure 1 (d) is a SEM image of Mo1S16 in the example; Figure 1 (e) is a SEM image of Mo1S24 in the embodiment.

[0027] Figure 2 These are transmission electron microscope (TEM) images of mercury adsorbents with different molybdenum-sulfur ratios in embodiments of the present invention; wherein, Figure 2 (a) is a TEM image of Mo8S1 in the embodiment; Figure 2 (b) is a TEM image of Mo2S1 in the example; Figure 2 (c) is a TEM image of MoS2 in the example; Figure 2 (d) is a TEM image of Mo1S16 in the example; Figure 2 (e) is a TEM image of Mo1S24 in the example.

[0028] Figure 3 For the analysis of the effects of different molybdenum-sulfur ratio mercury adsorbents on Hg in Example 4 of this invention 2+ The adsorption capacity histogram; where, Figure 3 (a) is a bar chart of the adsorption capacity of low sulfur-molybdenum-mercury adsorbents (Mo8S1, Mo4S1, Mo2S1, Mo1S1, MoS2). Figure 3 (b) is a bar chart of the adsorption capacity of high sulfur-molybdenum-mercury adsorbents (Mo1S4, Mo1S8, Mo1S12, Mo1S16, Mo1S20, Mo1S24).

[0029] Figure 4 In Example 5 of this invention, mercury adsorbents with different sulfur abundances were analyzed for their effects on Hg in the presence of coexisting cations. 2+ The selective adsorption results are shown in the figure; where, Figure 4 (a) The effect of the sulfur-depleted adsorbent Mo2S1 on Hg in binary and multi-component mixed systems. 2+ Removal rate; Figure 4 (b) The effect of normal MoS2 on Hg in binary and multi-component mixed systems 2+ Removal rate; Figure 4 (c) The effect of sulfur-rich adsorbent Mo1S16 on Hg in binary and multi-component mixed systems. 2+ Removal rate.

[0030] Figure 5 (a) K for mercury adsorbents with different sulfur abundances in Example 5 of this invention d Value distribution chart; Figure 5 (b) is a comparison chart of the mercury removal performance of mercury adsorbents with different sulfur abundances and other adsorbent materials in Example 5 of the present invention.

[0031] Figure 6 To illustrate the effects of mercury adsorbents with different sulfur abundances on Hg under different pH conditions in Example 6 of this invention. 2+ The removal rate and adsorption capacity are shown in the graph. Detailed Implementation

[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0033] Furthermore, the technical solutions of the various embodiments of the present invention can be combined with each other, but only if they are based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention.

[0034] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention, as well as the prior art known to those skilled in the art and the description of the invention, may be implemented using any prior art methods, devices, and materials similar to or equivalent to the methods, devices, and materials in the embodiments of the present invention.

[0035] This invention provides a mercury adsorbent based on sulfur abundance regulation, which is either a sulfur-poor mercury adsorbent or a sulfur-rich mercury adsorbent. The sulfur-poor mercury adsorbent and the sulfur-rich mercury adsorbent are prepared by hydrothermal reaction from precursors with a molar ratio of molybdenum to sulfur of 1:1-8:1 and 1:3-1:30, respectively.

[0036] This invention achieves precise control of the sulfur abundance of molybdenum sulfide materials by adjusting the molar ratio of molybdenum source to sulfur source in the precursor. As shown in Examples 1 and 2, when the molybdenum-sulfur molar ratio is controlled at 2:1, a sulfur-poor mercury adsorbent (denoted as Mo2S1) can be obtained; when the molybdenum-sulfur molar ratio is controlled at 1:16, a sulfur-rich mercury adsorbent (denoted as Mo1S16) can be obtained.

[0037] For example, the molar ratio of molybdenum to sulfur in the precursor can be 1:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2.0:1, 2.1:1, 2.2:1, 2.3:1, 2.4:1, 2.5:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, and any value between such a minimum and maximum value, or a range of any two values; or it can be 1:3, 1:5, 1:7, 1:10, 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:20, 1:25, 1:30, and any value between such a minimum and maximum value, or a range of any two values.

[0038] In some embodiments, the mercury adsorbent has an amorphous or short-range ordered structure with sulfur vacancy defects, exhibiting a nanoparticle stacking morphology.

[0039] The sulfur-depleted adsorbent Mo2S1 exhibits a nanoparticle stacked morphology with a loose structure and abundant grain boundary defects. TEM and HRTEM images show that it has poor crystallinity, mainly existing in amorphous or short-range ordered short cluster lattice forms. XRD analysis shows that its diffraction peaks are extremely weak and broad, further confirming its amorphous structural characteristics.

[0040] In some embodiments, the sulfur-rich mercury adsorbent has a two-dimensional layered structure with an interlayer spacing of 0.85-0.95 nm, and two-dimensional nanosheets with lattice defects distributed on their basal surface are assembled to form three-dimensional flower-like microspheres.

[0041] For example, the interlayer spacing of the sulfur-rich mercury adsorbent can be 0.85 nm, 0.86 nm, 0.87 nm, 0.88 nm, 0.89 nm, 0.90 nm, 0.91 nm, 0.92 nm, 0.93 nm, 0.94 nm, 0.95 nm, and any value between such a minimum and maximum value, or a range of any two values.

[0042] The mercury-sulfur-rich adsorbent Mo1S16 exhibits extremely fluffy, uniformly distributed three-dimensional flower-like microspheres with significantly thinner layers and increased wrinkles. TEM images show that the material has an extremely transparent, wrinkled film exhibiting two-dimensional graphene-like characteristics, with densely packed lattice defects on the basal plane. The interlayer spacing measured by TEM is 0.89-0.94 nm. XRD analysis shows that its characteristic diffraction peak is located at 2θ≈9.4°, and the interlayer spacing is calculated to be approximately 9.4 Å based on Bragg's law. The significantly increased interlayer spacing can effectively reduce Hg. 2+ The steric hindrance that diffuses inward creates an efficient physical mass transfer channel; basal lattice defects can break the originally inert basal plane and expose a large number of unsaturated high-energy active sulfur sites.

[0043] In some embodiments, the mercury adsorption capacity of the sulfur-poor mercury adsorbent is ≥2900 mg / g, and the partition coefficient K d ≥2.0×10 6 mL / g. In some embodiments, the mercury adsorption capacity of the sulfur-rich mercury adsorbent is ≥3900 mg / g, and the partition coefficient K d ≥1.0×10 8 mL / g.

[0044] For example, the mercury adsorption capacity of the sulfur-poor mercury adsorbent can be 2900 mg / g, 2950 mg / g, 3000 mg / g, 3050 mg / g, 3100 mg / g, 3150 mg / g, 3200 mg / g, and any value greater than or equal to 2900 mg / g, or a range of any two values.

[0045] For example, the mercury adsorption capacity of the sulfur-rich mercury adsorbent can be 3900 mg / g, 3950 mg / g, 4000 mg / g, 4050 mg / g, 4100 mg / g, 4150 mg / g, 4200 mg / g, and any value greater than or equal to 3900 mg / g, or a range of any two values.

[0046] For example, the partition coefficient K of the sulfur-poor mercury adsorbent d It can be 2.0×10 6 mL / g, 2.2×10 6 mL / g, 2.4×10 6 mL / g, 2.55×10 6 mL / g, 2.6×10 6 mL / g, 2.8×10 6 mL / g, 3.0×10 6 mL / g, and greater than or equal to 2.0 × 10 6 Any value of mL / g, or a range of any two values.

[0047] For example, the partition coefficient K of the sulfur-rich mercury adsorbent d It can be 1.0×10 8 mL / g, 1.2×10 8 mL / g, 1.4×10 8 mL / g, 1.6×10 8 mL / g, 1.67×10 8 mL / g, 1.8×10 8 mL / g, 2.0×10 8 mL / g, and greater than or equal to 1.0 × 10 8 Any value of mL / g, or a range of any two values.

[0048] In some embodiments, the Mo / S atomic ratio on the surface of the sulfur-poor mercury adsorbent is 0.1-0.5:1, and the Mo atoms on the surface of the adsorbent are... 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%, and the sulfur atoms on the surface contain S2 2- The proportion is 10-40%, S 2- The proportion is 50-80%, SO4 2- The proportion is 2-10%.

[0049] For example, the Mo / S atomic ratio on the surface of the mercury-poor sulfur adsorbent can be 0.1:1, 0.2:1, 0.3:1, 0.32:1, 0.33:1, 0.34:1, 0.35:1, 0.36:1, 0.37:1, 0.38:1, 0.39:1, 0.40:1, and any value between such a minimum and maximum value, or a range of any two values.

[0050] For example, the surface Mo of the sulfur-poor mercury adsorbent 4+ The percentage can be 60%, 65%, 70%, 72%, 74%, 76%, 78%, 80%, 85%, or any value between the minimum and maximum values, or a range consisting of any two values; Mo 6+ The percentage can be 10%, 12%, 14%, 16%, 18%, 20%, 25%, 30%, 35%, 40%, or any value between the minimum and maximum values, or a range of any two values; S2 2- The percentage can be 10%, 15%, 20%, 22%, 24%, 26%, 28%, 30%, 35%, 40%, or any value between the minimum and maximum values, or a range of any two values; S 2- The percentage can be 50%, 55%, 60%, 62%, 64%, 68%, 70%, 75%, 80%, or any value between the minimum and maximum values, or a range of any two values; SO4 2- The percentage can be 2%, 4%, 6%, 8%, 10%, or any value between the minimum and maximum values, or a range of any two values.

[0051] In some embodiments, the Mo / S atomic ratio on the surface of the sulfur-rich mercury adsorbent is 1:2.4-5.5, and the Mo atoms on the surface contain Mo atoms... 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%; S2 in surface sulfur atoms 2- The proportion is 20-50%, S 2- The proportion is 48-65%, SO4 2- The proportion is 10-15%.

[0052] For example, the Mo / S atomic ratio on the surface of the mercury-rich sulfur adsorbent can be 1:2.4, 1:3.0, 1:3.5, 1:4.0, 1:4.5, 1:5.0, 1:5.5, and any value between such a minimum and maximum value, or a range of any two values.

[0053] For example, the surface of the sulfur-rich mercury adsorbent contains Mo 4+The percentage can be 6.%, 65%, 70%, 71.46%, 72%, 74%, 75%, 80%, 85%, 90%, or any value between the minimum and maximum values, or a range consisting of any two values; Mo 6+ The percentage can be 10%, 11%, 12.93%, 13%, 14%, 20%, 25%, 30%, 35%, 40%, or any value between the minimum and maximum values, or a range of any two values; S2 2- The percentage can be 20%, 25%, 30%, 35%, 36%, 36.5%, 36.80%, 37%, 37.5%, 38%, 40%, 42%, 44%, 46%, 48%, 50%, as well as any value between the minimum and maximum values, or any range of any two values; S 2- The percentages can be 48%, 50%, 51%, 51.81%, 52%, 53%, 54%, 55%, 60%, 65%, as well as any value between the minimum and maximum values, or a range consisting of any two values; SO4 2- The percentage can be 10%, 11%, 12%, 14%, 15%, or any value between the minimum and maximum values, or any range of two values.

[0054] This invention provides a method for preparing any of the above-described mercury adsorbents, comprising the following steps: The precursor is obtained by mixing a molybdenum source with a sulfur source; the molar ratio of molybdenum to sulfur in the precursor is 1:1-8:1 or 1:3-1:30. The precursor is subjected to a hydrothermal reaction to obtain either the sulfur-poor mercury adsorbent or the sulfur-rich mercury adsorbent.

[0055] In some embodiments, the molybdenum source comprises ammonium heptamolybdate, and the sulfur source comprises thiourea.

[0056] In some more specific embodiments, a molybdenum source (such as ammonium heptamolybdate) and a sulfur source (such as thiourea) can be dissolved in deionized water at a set molybdenum-sulfur molar ratio, stirred evenly, and then transferred to a hydrothermal reactor for hydrothermal reaction. When the molybdenum-sulfur molar ratio is 2:1, a sulfur-poor mercury adsorbent Mo2S1 is obtained after the hydrothermal reaction; when the molybdenum-sulfur molar ratio is 1:16, a sulfur-rich mercury adsorbent Mo1S16 is obtained after the hydrothermal reaction.

[0057] In some embodiments, the hydrothermal reaction is carried out at a temperature of 100-250°C for a duration of 4-20 hours.

[0058] For example, the temperature of the hydrothermal reaction can be 100°C, 120°C, 150°C, 200°C, 220°C, 250°C, or any value between such a minimum and maximum value, or a range of any two values.

[0059] For example, the duration of the hydrothermal reaction can be 4 h, 8 h, 12 h, 16 h, 20 h, or any value between such a minimum and maximum, or a range of any two values.

[0060] This invention provides an application of the mercury adsorbent as described above or the mercury adsorbent prepared by the above method in the treatment of mercury-containing wastewater, comprising the steps of: contacting the mercury adsorbent with the mercury-containing wastewater to adsorb Hg in the mercury-containing wastewater. 2+ .

[0061] In some embodiments, the mercury-containing wastewater can be acidic wastewater generated during non-ferrous metal smelting. In use, the mercury adsorbent is directly added to the mercury-containing wastewater and, under stirring conditions, ensures full contact to adsorb Hg from the wastewater. 2+ This achieves the removal of mercury.

[0062] In some embodiments, the pH of the mercury-containing wastewater is ≥0; exemplarily, the pH of the mercury-containing wastewater can be >0.5, such as 0.5-2, 0.5-3, 0.5-5, 0.5-6, or 0.5-8; and exemplarily, the pH of the mercury-containing wastewater can be >1, such as 1-2, 1-3, 1-5, 1-6, 1-8, 1.5-2, 1.5-3, 1.5-5, 1.5-6, or 1.5-8.

[0063] Under extremely acidic conditions (pH=0), both the sulfur-poor and sulfur-rich mercury adsorbents maintained a removal rate of approximately 60% and an adsorption capacity of over 960 mg / g, while the removal rate of the normal MoS2 adsorbent dropped to around 42%. This indicates that the adsorbent described in this invention can maintain excellent mercury removal performance under strongly acidic conditions (pH=0-2), overcoming the technical bottleneck of traditional adsorbent materials being easily deactivated under strong acid conditions.

[0064] In some embodiments, the mercury-containing wastewater includes coexisting ions; When the mercury adsorbent is a sulfur-rich mercury adsorbent, the mercury-containing wastewater includes Cu. 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Cr 3+ At least one coexisting cation, or selected from Cl - F - HCO3 - PO43- At least one coexisting anion.

[0065] In some embodiments, when the mercury adsorbent is a sulfur-rich mercury adsorbent, the coexisting anions may include F. - HCO3 - PO4 3- At least one of them.

[0066] In some embodiments, the mercury-containing wastewater includes coexisting ions; In the case where the mercury adsorbent is a sulfur-poor mercury adsorbent, the coexisting cations include Cu. 2+ Co 2+ Ni 2+ Zn 2+ Cd 2+ Mn 2+ Fe 3+ Cr 3+ As 5+ At least one of them, or selected from Cl - F - HCO3 - PO4 3- At least one coexisting anion.

[0067] In some embodiments, when the mercury adsorbent is a sulfur-poor mercury adsorbent, the coexisting anions may include F. - HCO3 - PO4 3- At least one of them.

[0068] In some embodiments, the mercury-containing wastewater contains Hg 2+ The concentration of mercury is ≤2000mg / L, the dosage of the mercury adsorbent is 0.05-0.5g / L, the contact time between the mercury adsorbent and the mercury-containing wastewater is 5-600min, and the contact temperature is 0-100℃.

[0069] For example, the dosage of the mercury adsorbent can be 0.05 g / L, 0.10 g / L, 0.15 g / L, 0.20 g / L, 0.25 g / L, 0.30 g / L, 0.35 g / L, 0.40 g / L, 0.45 g / L, 0.50 g / L, and any value between such a minimum and maximum value, or a range of any two values.

[0070] For example, the contact time between the mercury adsorbent and the mercury-containing wastewater can be 30 min, 60 min, 90 min, 120 min, 150 min, 200 min, 300 min, 400 min, 500 min, 600 min, and any value between such a minimum and maximum value, or a range of any two values.

[0071] For example, the contact temperature between the mercury adsorbent and the mercury-containing wastewater can be 15°C, 20°C, 22°C, 25°C, 30°C, 35°C, 40°C, and any value between such a minimum and maximum value, or any range of two such values.

[0072] For example, the Hg in the mercury-containing wastewater 2+ The concentration can be 0 mg / L, 50 mg / L, 100 mg / L, 200 mg / L, 400 mg / L, 600 mg / L, 800 mg / L, 1000 mg / L, and any value between such minimum and maximum, or any range of two values.

[0073] To facilitate a further understanding of the present invention by those skilled in the art, the following examples are provided: Example 1 Preparation of the sulfur-poor mercury adsorbent Mo2S1: Ammonium heptamolybdate and thiourea were completely dissolved in 50 mL of deionized water and stirred vigorously at 300 rpm to obtain a precursor with a molar ratio of molybdenum to sulfur of 2:1. The precursor was then transferred to a 100 mL Teflon-lined autoclave and kept at 180 °C for 12 h. A black powder was collected by filtration, washed several times with deionized water and ethanol, and then dried in an oven at 80 °C for 10 h to obtain Mo₂S₁.

[0074] Preparation of mercury-sulfur-rich adsorbent Mo1S16: Ammonium heptamolybdate and thiourea were completely dissolved in 50 mL of deionized water and stirred vigorously at 300 rpm to obtain a precursor with a molar ratio of molybdenum to thiourea of ​​1:16. The precursor was then transferred to a 100 mL Teflon-lined autoclave and kept at 180 °C for 12 h. A black powder was collected by filtration, washed several times with deionized water and ethanol, and then dried in an oven at 80 °C for 10 h to obtain Mo1S16.

[0075] Example 2 Preparation of Mo8S1, Mo4S1, Mo1S1, MoS2, Mo1S4, Mo1S8, Mo1S12, Mo1S20, and Mo1S24: Ammonium heptamolybdate and thiourea were completely dissolved in 50 mL of deionized water and stirred vigorously at 300 rpm to obtain a precursor. The precursor was then transferred to a 100 mL Teflon-lined autoclave and kept at 180 °C for 12 h. A black powder was collected by filtration, washed several times with deionized water and ethanol, and then dried in an oven at 80 °C for 10 h to obtain the mercury adsorbent sample. Mo8S1 was prepared when the molybdenum-sulfur ratio in the precursor was 8:1. Mo4S1 was prepared when the molybdenum-sulfur ratio in the precursor was 4:1. Mo1S1 was prepared when the molybdenum-sulfur ratio in the precursor was 1:1. Mo1S2 was prepared when the molybdenum-sulfur ratio in the precursor was 1:2. Mo1S4 was prepared when the molybdenum-sulfur ratio in the precursor was 1:4. Mo1S8 was prepared when the molybdenum-sulfur ratio in the precursor was 1:8. Mo1S12 was prepared when the molybdenum-sulfur ratio in the precursor was 1:12. Mo1S20 was prepared when the molybdenum-sulfur ratio in the precursor was 1:20. Mo1S24 was prepared when the molybdenum-sulfur ratio in the precursor was 1:24.

[0076] Analysis example 1 like Figure 1 As shown, SEM tests were performed on mercury adsorbents with different molybdenum-sulfur ratios. Figure 1 (a) is the SEM image of Mo8S1. Figure 1 (b) is a SEM image of Mo2S1. Figure 1 (c) is a SEM image of MoS2. Figure 1 (d) is the SEM image of Mo1S16. Figure 1 (e) is the SEM image of Mo1S24. As can be seen from the figure, with the increase of sulfur abundance, the morphology of the sample went through an evolution process from "dense bulk" to "loose particles", then to "three-dimensional flower-like network" and finally "aggregation and densification".

[0077] Under extremely sulfur-deficient conditions (Mo8S1), the product exhibits dense, massive aggregates with smooth surfaces and a lack of pores, indicating that the scarcity of sulfur sources limits the anisotropic growth of crystals. When the molybdenum-sulfur ratio increases to 2:1 (Mo2S1), the massive aggregates disintegrate into smaller nanoparticle stacks, increasing structural porosity. This irregular stacking is often accompanied by abundant grain boundary defects, which facilitates the exposure of unsaturated active sites.

[0078] Normal MoS2 exhibits typical molybdenum disulfide nanoflora characteristics, composed of rolled-up sheets, but the sheets are stacked relatively tightly.

[0079] The sulfur-rich Mo1S16 adsorbent consists of extremely fluffy, uniformly distributed three-dimensional flower-like microspheres with significantly thinner sheets and increased wrinkles. This highly open, multi-level network structure not only maximizes the exposure area of ​​active sites but also enhances the adsorption capacity of Hg. 2+ The diffusion of sulfur provides abundant mass transfer channels. However, excessive sulfur (Mo1S24) can lead to overgrowth and secondary aggregation of nanoflora, causing partial pore blockage and reducing site accessibility.

[0080] like Figure 2 As shown, TEM tests were performed on mercury adsorbents with different molybdenum-sulfur ratios. Figure 2 (a) is a TEM image of Mo8S1. Figure 2 (b) is a TEM image of Mo2S1. Figure 2 (c) is a TEM image of MoS2. Figure 2 (d) is a TEM image of Mo1S16. Figure 2 (e) is a TEM image of Mo1S24. It can be seen that as the sulfur abundance gradually increases, the morphology of the adsorbent gradually changes from "dense blocky" to "highly exfoliated two-dimensional sheet structure".

[0081] For sulfur-poor materials with sulfur abundance below the normal stoichiometry (such as Mo8S1 and Mo2S1), their crystallinity is poor, mainly existing in the form of amorphous or short-range ordered short cluster lattices with interlayer spacing of 7.02-7.1 Å. When the normal stoichiometry is reached (MoS2), relatively clear layered molybdenum sulfide lattice fringes appear inside the sample, with an interlayer spacing of approximately 0.64 nm, which conforms to the standard interlayer spacing of typical 2H-MoS2.

[0082] Further increasing the sulfur abundance to a sulfur-rich ratio (Mo1S16) results in significant changes to the material's lattice structure: on the one hand, dense lattice defects on the basal planes break down the originally inert planes, exposing a large number of unsaturated, high-energy active sulfur sites; on the other hand, the interlayer spacing widens significantly, extending to 0.89-0.94 nm. This anomalous lattice expansion is due to the embedding of excessive amorphous active sulfur (such as polysulfide species) into the interlayer gaps of molybdenum sulfide during synthesis. The significantly expanded interlayer spacing effectively reduces Hg. 2+ Spatial steric hindrance that diffuses inward creates an efficient physical mass transfer channel.

[0083] From a morphological perspective, sulfur-rich Mo1S16 materials exhibit extremely transparent, wrinkled films, indicating that they possess extremely thin, two-dimensional graphene-like characteristics. However, when sulfur abundance is excessive (Mo1S24), the highly exfoliated ultrathin sheets are affected by surface energy, resulting in secondary agglomeration and re-agglomeration, leading to a decrease in specific surface area and openness.

[0084] Analysis example 2 XRD analysis was performed on mercury adsorbents with different molybdenum-sulfur ratios. MoS2 showed good agreement with the standard 2H phase MoS2 (JCPDSPDF#37-1492), with an interlayer spacing of approximately 6.11 Å, exhibiting two-dimensional layered characteristics but weak overall crystallinity. In contrast, the diffraction peaks of the sulfur-poor samples (Mo:S = 8:1 and 2:1) were extremely weak and broad, further confirming their amorphous or short-range ordered structural characteristics, consistent with TEM observations.

[0085] With a significant increase in sulfur abundance, the phase structure of the sulfur-rich mercury adsorbent Mo1S16 underwent a significant change. The corresponding interlayer spacing increased to approximately 9.4 Å, an increase of about 3.3 Å compared to ordinary MoS2. This confirms that the excess sulfur source successfully induced the intercalation of active sulfur species into the lattice, constructing a two-dimensional layered framework with an ultra-large interlayer spacing, thereby providing a suitable adsorbent for Hg. 2+ It provides an extremely wide physical channel for rapid entry and deep diffusion.

[0086] Interlayer vibrational modes of mercury adsorbents with different molybdenum-sulfur ratios were analyzed. Compared with normal MoS2, the E0 of the sulfur-depleted sample Mo2S1 was significantly higher. 1 2g The peak half-width is significantly increased, and the peak shape is significantly broadened. This phenomenon is attributed to the disruption of lattice periodicity, confirming that reducing sulfur abundance induces a large number of structural defects such as sulfur vacancies in the crystal.

[0087] In addition, the E values ​​of sulfur-poor Mo2S1 and sulfur-rich Mo1S16 samples... 1 2g With A 1g The peak intensity ratios were 1.63 and 4.4, respectively, both significantly higher than those of conventional MoS2, demonstrating that these two modified samples exposed more boundary surfaces and unsaturated active sites.

[0088] The combined Raman analysis results show that regulating the sulfur abundance of the precursor can effectively alter the microstructure of molybdenum sulfide, significantly increasing the concentration of edge defects, thereby providing a basis for Hg production. 2+ The capture provides a vast number of high-energy binding sites.

[0089] Analysis example 3 As shown in Table 1, the surface elemental composition of adsorbents with different sulfur abundances was analyzed by X-ray photoelectron spectroscopy.

[0090] S2 with high electron cloud polarization 2- The group is related to "soft acid" Hg 2+ The core active site undergoes strong covalent coordination, while the low-valence Mo... 4+ It then participates in redox reactions as an electron donor, donating some Hg. 2+ It is reduced to elemental mercury. It is evident that an appropriate level of sulfur abundance not only maintains the highly reduced state and stability of the structure, but also promotes the exposure of more polysulfide active terminals on the basal surface and edges.

[0091] However, when the sulfur source is in extreme excess, the Mo in the Mo1S24 sample... 4+ With S2 2- The content actually dropped to 63.37% and 34.08%, Mo 6+ The percentage increased to 22.46%, indicating that excessive sulfur intercalation or disordered accumulation may cause instability in the surface structure, which in turn weakens the exposure rate of active sites.

[0092] In summary, whether by directly introducing a large number of polysulfide active groups by increasing sulfur abundance or by inducing the generation of defective unsaturated sulfur bonds by reducing sulfur abundance, both methods can effectively break the lattice inertness of conventional MoS2 and significantly improve the abundance of active sulfur sites on the material surface.

[0093] Table 1. Elemental valence states (%) on XPS surfaces with different proportions of adsorbents Analysis example 4 Adsorption capacity test.

[0094] The adsorption experiment was conducted at pH=2, Hg 2+ The initial concentration was 200 mg·L. -1 The mercury adsorbent dosage was 10 mg, and the solution volume was 100 mL. The mixture was stirred at 380 rpm for 12 h at room temperature to ensure the adsorption process proceeded fully. After the reaction, the solution was filtered through a 20 μm filter, and the mercury concentration in the solution before and after adsorption was determined using a LUMEX-RA-915 liquid mercury analyzer.

[0095] Mercury adsorption capacity of adsorbents with different molybdenum-sulfur ratios, such as Figure 3 As shown, where Figure 3 (a) Bar chart of adsorption capacity of low sulfur-molybdenum-mercury ratio adsorbent materials (Mo8S1, Mo4S1, Mo2S1, Mo1S1, MoS2), Figure 3 (b) Bar chart of adsorption capacity of high sulfur-molybdenum-mercury adsorbent materials (Mo1S4, Mo1S8, Mo1S12, Mo1S16, Mo1S20, Mo1S24).

[0096] visible, Figure 3 In (a), as the sulfur-molybdenum ratio decreases, the adsorption capacity shows a trend of first increasing and then decreasing, reaching a peak adsorption capacity of 2951 mg / g (denoted as Mo2S1) when Mo:S = 2:1. Figure 3 As shown in (b), the adsorption capacity also exhibits a trend of first increasing and then decreasing with the increase of the sulfur-molybdenum ratio, reaching a maximum value of 3956 mg / g (denoted as Mo1S16) when Mo:S = 1:16. The above results indicate that sulfur abundance has a significant impact on the adsorption performance of MoS2, and appropriate sulfur regulation can effectively optimize the structure of active sites, thereby constructing a high-performance mercury adsorbent.

[0097] Analysis example 5 The effect of different sulfur abundances on the selective mercury removal performance of molybdenum disulfide adsorbents was investigated.

[0098] like Figure 4 As shown, the study investigated the effects of sulfur-poor adsorbent Mo2S1, normal MoS2, and sulfur-rich mercury-rich adsorbent Mo1S16 on binary and multi-component mixed systems (Pb). 2+ Cu 2+ Co 2+ Ni 2+ Zn 2+ Cd 2+ Mn 2+ Fe 3+ Cr 3+ As 5+ Mercury selectivity was tested by adding 10 mg of adsorbent to 100 mL of solution containing 200 mg·L⁻¹. -1 Hg 2+ The removal rate of each ion was measured after reacting in a mixed solution of ions and interfering ions of equal concentration for 12 hours.

[0099] The results show that sulfur abundance plays a decisive role in the material's resistance to interference. For example... Figure 4 As shown in (b), firstly, normal MoS2 exhibits extreme susceptibility to disturbances in binary systems. Compared to single-component systems, it is more susceptible to disturbances related to Hg. 2+ The adsorption capacity decreased significantly; especially when combined with Pb. 2+ When coexisting, this adsorbent is effective against Pb. 2+ The removal rate was 68%, surpassing that of Hg. 2+ The removal rate was 39%; while compared with Ni 2+ Fe 3+ and As 5+ Coexistence or in a multi-component mixture system, its effect on Hg 2+ The removal rate drops to almost 10% or even approaches 0. This indicates that the surface active sites of molybdenum sulfide in conventional proportions are limited and easily occupied by other cations or lose activity due to competition.

[0100] like Figure 4 As shown in (a), the anti-interference ability of the sulfur-depleted adsorbent Mo2S1 is improved, and it is effective in most binary systems against Hg. 2+ It maintained a removal rate of over 80%. However, its resistance to certain ions remains weak. For example, Cd... 2+ and Pb 2+ The presence of Fe reduced its mercury removal rates to 47% and 59%, respectively; while Fe 3+ And As 5+ The presence of a multi-component mixed system leads to the near-complete loss of the material's adsorption capacity, with a removal rate of less than 10%.

[0101] like Figure 4 As shown in (c), the sulfur-rich mercury adsorbent Mo1S16 exhibits excellent Hg adsorption capacity. 2+ High selectivity. Whether in a binary system with ten single interfering ions or in an extremely demanding eleven-ion mixture, this material exhibits high selectivity for Hg. 2+ The removal rates consistently remained above 90%. Except for Pb... 2+ Aside from about 20% co-adsorption, the adsorption of other interfering ions is extremely low.

[0102] The sulfur-poor adsorbent Mo2S1, normal MoS2, and sulfur-rich mercury-rich adsorbent Mo1S16 were also studied in binary and multi-component mixed systems (Cl). - F - HCO3 - and PO4 3- Mercury selectivity under different anions. 2+ The effects of adsorption vary significantly. For F - HCO3 - and PO4 3- All three adsorbents exhibited excellent anti-interference capabilities. In the binary system where these three anions were present respectively, the three adsorbents showed good resistance to Hg. 2+ The removal rates remained close to 100%. However, Cl - The existence of Hg 2+ The removal of [the substance] produced a significant inhibitory effect.

[0103] like Figure 5 As shown, the selectivity of the adsorbent for Hg and its competitiveness in practical applications were further quantitatively studied.

[0104] like Figure 5 As shown in (a), the allocation coefficient K is introduced. d This key parameter is used to evaluate the adsorbent's effect on Hg. 2+ Its capture ability and affinity. It is generally believed that when K... d >105 mL·g -1 At this time, the adsorbent exhibits excellent affinity for this ion. The K2 of normal MoS2... d The value is 9.33 × 10 4 mL·g -1 K of desulfurized Mo2S1 d The value was increased to 2.55 × 10. 6 mL·g -1 Sulfur-rich Mo1S16 exhibits an extremely remarkable affinity, with its K... d The value is as high as 1.67 × 10 8 mL·g -1 It far surpasses other adsorbents and can react with Hg. 2+ It generates extremely strong specific binding force, thus achieving efficient enrichment of mercury even at extremely low concentrations.

[0105] like Figure 5 As shown in (b), the mercury removal performance of the best-performing sulfur-rich mercury adsorbent Mo1S16 and the sulfur-poor adsorbent Mo2S1 was systematically compared with that of other adsorbent materials.

[0106] Most reported heavy metal adsorbents, including conventional sulfides, MOFs, and other modified MoS2 materials, generally operate within a weakly acidic to neutral pH range: pH 3.0–10.0. Under strongly acidic conditions (pH < 2.0), these materials often face problems such as structural instability, active site dissolution, or intense proton competition, leading to a significant limitation in adsorption capacity. For example, some sulfide-based materials, such as CuS2… x Although TiO2 and Fe2TiO5 sulfide can operate in an environment with pH=2.0, their maximum saturation adsorption capacity is only maintained at 300 mg·g⁻¹. -1 While the modified W-DR-N-MoS2 and MoS2-HNR achieved adsorption capacities of 2506 mg / g and 1991 mg / g, respectively, they were not suitable for extremely acidic systems. In contrast, the adsorbent materials prepared in this study not only maintained structural and performance stability under extremely strong acidic conditions at pH=2, but also exhibited adsorption capacities of approximately 3000 mg / g and 4000 mg / g, respectively, far exceeding the vast majority of similar materials.

[0107] Analysis example 6 The effect of pH on mercury adsorption performance was investigated.

[0108] The effects of strongly acidic conditions (pH 0-2.0) on the mercury removal performance of three adsorbents with different sulfur abundances were investigated. Figure 6 As shown. 10 mg of adsorbent was weighed and added to 100 mL of Hg solution with an initial concentration of 200 mg / L. 2+In the solution, the pH values ​​were adjusted to 0, 1.0, 1.5, and 2.0 using sulfuric acid and sodium hydroxide, respectively. The solution was stirred at 380 rpm for 12 hours at room temperature (25℃) to ensure the adsorption process proceeded fully. After the reaction, the solution was filtered through a 20 μm filter, and the mercury concentration in the solution before and after adsorption was measured using a LUMEX-RA-915 liquid mercury analyzer. The removal rate and adsorption capacity were then calculated.

[0109] from Figure 6 It is evident that the solution pH value has a significant regulatory effect on the adsorption process, and the three adsorbents exhibit similar pH-dependent patterns. Within the pH range of 1.0-2.0, all three materials demonstrate excellent mercury removal performance, effectively removing Hg. 2+ The removal rate remained stable at over 98%, even approaching 100%, with a corresponding saturated adsorption capacity as high as 2000 mg / g. This indicates that the active sites on the material surface are highly active in weakly acidic to moderately strong acidic environments. When the solution acidity further increases to extreme conditions of pH < 1.0, the adsorption efficiency decreases to varying degrees. In an extremely acidic environment of pH = 0, the removal rate of normal MoS2 adsorbent drops to about 42%; while sulfur-poor Mo2S1 and sulfur-rich Mo1S16 adsorbents exhibit relatively stronger acid resistance, still maintaining a removal rate of about 60% and an adsorption capacity of over 960 mg / g.

[0110] Analysis example 7 Study on the adsorption mechanism of mercury-rich sulfur adsorbent.

[0111] 10 mg of adsorbent Mo1S16 was added to 100 mL, resulting in an initial concentration of 200 mg·L⁻¹. -1 Hg 2+ In the solution, samples before and after the reaction were collected for characterization by X-ray photoelectron spectroscopy and mercury temperature-programmed desorption.

[0112] To clarify the effect of sulfur-rich mercury adsorbents on Hg 2+ The capture mechanism of Hg was characterized by X-ray photoelectron spectroscopy (XPS) before and after adsorption, indicating that Hg... 2+ It has been successfully loaded onto the material surface.

[0113] Analysis of the Hg4f spectrum confirmed that the active sulfur sites on the adsorbent surface are related to Hg. 2+ A strong chemical coordination occurred, resulting in a stable compound dominated by Hg-S covalent bonds.

[0114] Further analysis of the adsorption product's speciation was conducted using mercury temperature-programmed desorption (Hg-TPD) to analyze the post-adsorption sample, revealing some Hg. 2+ It is reduced in situ to Hg by the reducing sites on the material surface. 0 This reveals the existence of a synergistic "adsorption-reduction" mechanism.

[0115] The subsequent temperature-induced desorption curves further revealed the form in which chemisorbed mercury existed, indicating that Hg... 2+ Not only are conventional surface coordination complexes formed on the surface of sulfur-rich materials, but they are also further transformed into crystalline mercury sulfide with extremely high thermal stability through lattice rearrangement.

[0116] In summary, based on XPS and Hg-TPD results, it is inferred that the sulfur-rich Mo1S16 adsorbent has a significant effect on Hg adsorption. 2+ The capture of Hg may follow a unique "dual mercury fixation mechanism": a portion of Hg... 2+ Reduced to elemental Hg 0 One portion is physically enriched, while the other portion undergoes strong chemical bonding with reactive sulfur to form stable β-HgS and α-HgS. This synergistic effect of "electron transfer + Hg-S coordination" may be the fundamental reason why this material achieves ultra-high adsorption capacity and excellent environmental stability.

[0117] To further verify the above, as shown in Table 2, peak separation was performed on Mo3d and S2p to further analyze the changes in the content of active sites participating in the adsorption reaction.

[0118] Table 2. Valence ratios of surface elements before and after mercury removal from Mo1S16 Mo before and after mercury removal 4+ The atomic percentage of Mo decreased from 71.46% to 65.55%. 6+ The atomic proportion of Mo increased from 12.93% to 19.08% during the Hg reduction process. 4+ Oxidized into Mo 6+ This proves Mo 4+ The site exhibits extremely strong reducing activity, which is crucial for capturing Hg. 2+ During the process, it underwent oxidation as the main electron donor; before and after adsorption, unsaturated sulfur S2... 2- The proportion decreased from 36.80% to 30.36%, while S 2- and SO4 2- The proportions increased from 50.63% and 11.39% to 56.93% and 12.27% respectively, unsaturated S2 2- The significant reduction and SO4 2- The increase in Hg indicates that some low-valence sulfur species are involved in the reduction of Hg. 2+ Restored to Hg 0 The electron transfer process also indicates the high activity of unsaturated S2 2- The group forms a stable Hg-S bond with Hg through bond breaking or orbital hybridization.

[0119] In summary, the changes in Mo3d and S2p spectra before and after mercury removal from Mo1S16 were analyzed by peak fitting. Compared with before mercury removal, the changes in Mo3d and S2p spectra after mercury removal from Mo1S16 were significant. 4+ Content and unsaturated S2 2- The content of all samples decreased to some extent, indicating that the adsorbent Mo on the surface of sulfur-rich Mo1S16 was reduced. 4+ With unsaturated S2 2- During Hg adsorption, both the Hg and the target pollutant not only act as strong affinity sites for direct chemical anchoring, but also successfully transfer Hg via interfacial charge transfer. 2+ Hg reduced to a stable state 0 .

[0120] Analysis example 8 Study on the adsorption mechanism of sulfur-poor adsorbents.

[0121] 10 mg of adsorbent Mo2S1 was added to 100 mL, resulting in an initial concentration of 200 mg·L⁻¹. -1 Hg 2+ The solid samples before and after the reaction were characterized by XPS and Hg-TPD in solution.

[0122] The adsorbed Mo2S1 sample exhibited a characteristic Hg4f peak in the binding energy range of 100-105 eV, confirming the successful loading of mercury on the material surface. Analysis of the Hg4f spectrum confirmed that the active sites on the surface of the sulfur-depleted MoS21 adsorbent can also bind with Hg. 2+ A strong chemical coordination occurs, forming a stable mercury sulfide compound.

[0123] Hg-TPD was used to analyze the desorption of the adsorbed samples, indicating that even in a sulfur-deficient state, the reducing sites exposed by lattice defects on the material surface can still induce redox reactions, removing some Hg. 2+ Converted to Hg 0 .

[0124] XPS spectra of Mo3d and S2p on the adsorbent surface before and after the reaction were compared and analyzed. This indicates that the adsorbent effectively captures Hg in a sulfur-poor environment. 2+ During this process, the Mo and S elements on the surface also act as key electron donors. They undergo oxidation by losing some electrons, driving electrons to the Hg adsorbed at the solid-liquid interface. 2+ Targeted transfer. This result is highly consistent with the pattern observed in mercury-rich sulfur adsorbents.

[0125] As shown in Table 3, peak separation was performed on Mo3d and S2p to further analyze the changes in the content of active sites involved in the adsorption reaction, and the Mo content before and after mercury removal was analyzed. 4+ The atomic percentage of Mo decreased from 74.88% to 71.26%. 6+The atomic proportion of Mo increased from 14.47% to 17.42%, a trend consistent with that of the sulfur-rich system, confirming the presence of low-valence Mo in the sulfur-poor system. 4+ Capture Hg 2+ During the process, it also underwent oxidation as the main electron donor; after adsorption, the sulfur lattice on the surface of the sulfur-depleted Mo2S1 sample was subjected to oxidation. 2- The proportion decreased from 68.15% to 47.41%, while SO4 2- The proportion of sulfur increased from 4.77% to 15.06%, indicating that in the sulfur-poor system, sulfur species mainly participate in adsorption, forming stable Hg-S bonds with Hg. Furthermore, after the reaction, S2... 2- The abnormal increase in the proportion, from 27.08% to 37.53%, may be due to the S lattice. 2- This is due to the formation of intermediate disulfide bonds during the oxidative reconstruction process.

[0126] Table 3. Valence ratios of surface elements before and after mercury removal from Mo2S1 In summary, comparing sulfur-rich mercury adsorbents and sulfur-poor adsorbents, it can be seen that regardless of sulfur abundance, both materials achieve the desired performance through Mo... 4+ Co-oxidation with low-valence sulfur species achieves the oxidation of Hg 2+ The reduction and fixation; the main difference is that sulfur-rich materials mainly utilize S2 2- Sites achieve Hg 2+ Capture and reduction, while sulfur-depleted materials rely more on lattice S 2- with Mo 4+ The synergistic effect of Hg 2+ Adsorption.

[0127] Analysis example 9 The specific surface area and pore structure of adsorbents with different sulfur abundances were analyzed by BET analysis, and the N2 adsorption isotherms and pore size distributions of different materials were determined.

[0128] Table 4. Specific surface area, pore volume, and average pore size of mercury adsorbents with different molybdenum-sulfur ratios. Samples with different sulfur abundances all exhibited type III isotherm characteristics, indicating a weak interaction between the adsorbent and N2 molecules, and that the materials are predominantly mesoporous. The pore sizes of the sulfur-rich samples MoS24, MoS16, and normal MoS2 are mainly concentrated in the 2-50 nm range, with a relatively uniform pore distribution and a low proportion of macropores larger than 50 nm. The pore size of the sulfur-depleted sample Mo2S1 is concentrated in the 2-40 nm range, with relatively abundant micropores in the 2-10 nm range; the overall pore size distribution is slightly narrower than that of the sulfur-rich and normal samples. The further sulfur-depleted Mo8S sample has a dense structure, with a significant reduction in the number of pores in all pore size ranges.

[0129] Table 4 shows the specific surface area, pore volume, and pore size of samples with different sulfur abundances. The results indicate that all samples are mesoporous, and the specific surface area and pore volume generally increase with increasing sulfur abundance. MoS24 has the highest specific surface area, while the specific surface area and pore volume of MoS16 are similar to those of normal MoS2. Normal MoS2 has the largest average pore size. With decreasing sulfur abundance, the specific surface area and pore volume decrease significantly.

[0130] The above technical solutions of the present invention are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. All equivalent structural transformations made under the technical concept of the present invention using the contents of the present invention specification and drawings, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.

Claims

1. A mercury adsorbent based on sulfur abundance regulation, characterized in that, The adsorbent is either a sulfur-poor mercury adsorbent or a sulfur-rich mercury adsorbent. The sulfur-poor mercury adsorbent is prepared by hydrothermal reaction from a precursor with a molybdenum-sulfur molar ratio of 1:1 to 8:1, and the sulfur-rich mercury adsorbent is prepared by hydrothermal reaction from a precursor with a molybdenum-sulfur molar ratio of 1:3 to 1:

30. The sulfur-poor mercury adsorbent has an amorphous or short-range ordered structure with sulfur vacancy defects, exhibiting a nanoparticle stacking morphology. The sulfur-rich mercury adsorbent is assembled from two-dimensional nanosheets with lattice defects distributed on the basal surface to form three-dimensional flower-like microspheres.

2. The mercury adsorbent based on sulfur abundance regulation according to claim 1, characterized in that, The mercury adsorption capacity of the low-sulfur mercury adsorbent is ≥2900 mg / g, and the partition coefficient K d ≥2.0×10 6 mL / g; The mercury adsorption capacity of the sulfur-rich mercury adsorbent is ≥3900 mg / g, and the partition coefficient K d ≥1.0×10 8 mL / g.

3. The mercury adsorbent based on sulfur abundance regulation according to claim 1, characterized in that, The surface Mo / S atomic ratio of the sulfur-poor mercury adsorbent is 0.1-0.5:1, and the Mo atoms in the surface molybdenum atoms are... 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%, and the sulfur atoms on the surface contain S2 2- The proportion is 10-40%, S 2- The proportion is 50-80%, SO4 2- The proportion is 2-10%; The surface Mo / S atomic ratio of the sulfur-rich mercury adsorbent is 1:2.4-5.5, and the Mo atoms in the surface molybdenum atoms are... 4+ The proportion is 60-90%, Mo 6+ The proportion is 10-40%; S2 in surface sulfur atoms 2- The proportion is 20-50%, S 2- The proportion is 48-65%, SO4 2- The proportion is 10-15%.

4. A method for preparing the mercury adsorbent according to any one of claims 1-3, characterized in that, Including the following steps: The precursor is obtained by mixing a molybdenum source with a sulfur source; the molar ratio of molybdenum to sulfur in the precursor is 1:1-8:1 or 1:3-1:

30. The precursor is subjected to a hydrothermal reaction to obtain either the sulfur-poor mercury adsorbent or the sulfur-rich mercury adsorbent.

5. The method for preparing the mercury adsorbent according to claim 4, characterized in that, The hydrothermal reaction is carried out at a temperature of 100-250℃ for a duration of 1-20 hours.

6. The application of a mercury adsorbent according to any one of claims 1-3 or a mercury adsorbent prepared by the preparation method according to claim 4 or 5 in the treatment of mercury-containing wastewater, characterized in that, The steps include: the mercury adsorbent is contacted with the mercury-containing wastewater to adsorb Hg from the wastewater. 2+ .

7. The application of the mercury adsorbent according to claim 6 in the treatment of mercury-containing wastewater, characterized in that, The pH of the mercury-containing wastewater is ≥0.

8. The application of the mercury adsorbent according to claim 6 in the treatment of mercury-containing wastewater, characterized in that, The mercury-containing wastewater contains coexisting ions; When the mercury adsorbent is a sulfur-rich mercury adsorbent, the mercury-containing wastewater includes Cu. 2+ Co 2+ Ni 2+ Zn 2+ Mn 2+ Cr 3+ At least one coexisting cation, or Cl - F - HCO3 - PO4 3- At least one coexisting anion.

9. The application of the mercury adsorbent according to claim 6 in the treatment of mercury-containing wastewater, characterized in that, The mercury-containing wastewater contains coexisting ions; When the mercury adsorbent is a sulfur-poor mercury adsorbent, the mercury-containing wastewater includes Cu. 2+ Co 2+ Ni 2+ Zn 2+ Cd 2+ Mn 2+ Fe 3+ Cr 3+ As 5+ At least one coexisting cation, or Cl - F - HCO3 - PO4 3- At least one coexisting anion.

10. The application of the mercury adsorbent according to claim 6 in the treatment of mercury-containing wastewater, characterized in that, The mercury-containing wastewater contains Hg 2+ The concentration of mercury is ≤2000mg / L, the dosage of the mercury adsorbent is 0.01-2g / L, the contact time between the mercury adsorbent and the mercury-containing wastewater is 5-600min, and the contact temperature is 0-100℃.